2014
DOI: 10.4049/jimmunol.1301761
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously Expressed IL-13Rα2 Attenuates IL-13–Mediated Responses but Does Not Activate Signaling in Human Lung Fibroblasts

Abstract: IL-13 can bind to two distinct receptors: a heterodimer of IL-13Rα1/IL-4Rα and IL-13Rα2. Whereas IL-13Rα1/IL-4Rα engagement by IL-13 leads to the activation of STAT6, the molecular events triggered by IL-13 binding to IL-13Rα2 remain incompletely understood. IL-4 can bind to and signal through the IL-13Rα1/IL-4Rα complex but does not interact with IL-13Rα2. Idiopathic pulmonary fibrosis is a progressive and generally fatal parenchymal lung disease of unknown etiology with no current pharmacologic treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
7
50
0
1
Order By: Relevance
“…In line with this notion, elevated levels of IL-4 were measured in IPF bronchial alveolar lavage fluid (BALF) and an increased expression of the IL-4 and IL-13 receptors was detected in IPF lung fibroblasts [5,6,7]. In addition, IL-4 deficient mice or mice with targeted disruption of the key components of the IL-4 signaling pathway were found to be protected against pulmonary fibrosis [8,9].…”
Section: Introductionmentioning
confidence: 73%
“…In line with this notion, elevated levels of IL-4 were measured in IPF bronchial alveolar lavage fluid (BALF) and an increased expression of the IL-4 and IL-13 receptors was detected in IPF lung fibroblasts [5,6,7]. In addition, IL-4 deficient mice or mice with targeted disruption of the key components of the IL-4 signaling pathway were found to be protected against pulmonary fibrosis [8,9].…”
Section: Introductionmentioning
confidence: 73%
“…Using STAT6 knockout mice that were sensitized with house dust mites, a study demonstrated that STAT6 was a major transcription factor for producing periostin [20]. Furthermore, STAT6 siRNA decreased periostin expression in lung fibroblasts [24]. Subsequently, the ERK1/2 pathway, as well as the JAK/STAT6 pathway, has also been shown to be important for periostin production in human airway epithelial cells cultured at an air-liquid interface [25] and in human lung fibroblasts [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IL-13 first binds to the IL13Ra1 chain, leading to the recruitment of the IL-4Ra chain. Another chain, termed IL-13Ra2, also binds IL-13; there is an ongoing controversy as to whether IL-13Ra2 acts as a decoy receptor attenuating IL-13-driven fibrosis [154,155] or its triggering induces TGF-b, which in turn acts profibrotically [156,157]. Activation of the IL-4R complexes initiates complex intracellular signaling utilizing members of the JAK family of tyrosine kinases, the IRS family of proteins, STAT6, and other intracellular signaling mediators (reviewed in [153]).…”
Section: Pdgfmentioning
confidence: 99%